THE OMNIBUS LAW ON JOB CREATION AND PANCASILA AS THE LEGAL IDEOLOGY IN INDONESIA - Iwan Iwan; Farida Farida; Fitri Pratiwi; Zahri Aeniwati; Siti Laelatussofah (Jurnal Pembaharuan Hukum, 2020)
Pancasila is used as a paradigm in law in Indonesia. As a legal development paradigm, Pancasila requires that development in society be the starting point for the existence of a legal product. The purpose of this study is that to explore the value of Pancasila as a Legal Development Paradigm and its implementation in the Omnibus Law On Job Creation. This research method uses the normative method. The result of this research is that Pancasila in the prevailing statutory regulations is the Grud norm which will cover the entire contents of the Constitution. The Omnibus Law Law on job creation is intended as a law made to revoke or change several laws at once. Thus, the omnibus Law that is made is a new legal model or a new paradigm in legislation in Indonesia.